Zume hauekin… ekin lanari. Reflexiones sobre la génesis, naturaleza e inserción de la Ley de Instituciones Locales de Euskadi en el peculiar sistema de fuentes del Derecho vasco - Santiago Larrazabal Basañez (Revista Vasca de Administración Pública)
This article describes first the process of negotiation and approval of Act 2/2016 of April 7th on Local Entities of Euskadi. Secondly, it carries out a detailed study of its nature as comprehensive act, being part of the «hard core» of the Basque institutional system, which puts an end to the three institutional levels of Euskadi and that by developing the Statute and the basic legislation regarding local regime, and by virtue of the possibilities of updating of the Basque historic rights, covered by the Constitution, it establishes its own local regime, that of the Basque foral municipality. An Act that defines competences among the different Basque institutional levels with a tough defence of local autonomy of Basque local entities without prejudice of reinforcing some competences of the Historic territories, specially in the field of local finances. Thirdly, the position of the Local Entities Act within the complex framework of the sources of Basque Law is studied, reaching the conclusion that it can be considered an act with a statutory task, being accordingly part of the so called statutory block. Fourthly, we refer to how this Act needs a special protection against possible tacit amendments thereto which could jeopardize the role that plays as one of the pillars of the legalinstitutional framework of the Basque self-government. Finally, the article ends with some brief conclusions which summarize the main ideas defended along it and with a personal assessment of the author regarding the Act.